The development of real-time pcr for the detection of bacteraemia - Shieng, Gooi Choo (Universiti Sains Malaysia, 2016)
Bacteraemia occurs when bacteria invade the bloodstream. It is associated with inflammatory response such as fever, increased heart rate, hypotension, breathing difficulty, and may lead to multiple organ failures or subsequent death. Bacteraemia has mortality rate, ranging from-to -with nearly one-quarter to about two-third fatality cases. Early detection of bacteraemia is important in cl